Phonological awareness skills of a group of Grade 4 learners in a multi-cultural, multi-lingual education context with English as Language of Learning and Teaching (ELoLT) - Avenant, Carina (University of Pretoria, 2013)
Dissertation (M (Communication Pathology))--University of Pretoria, 2007.